(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2026)
Probabilities theory random of events event to give probability based on other of events probability determination with practitioner mathematics from networks is one. Each of the event face to give probability is close to 1 if so , it in practice almost to consider inevitable possible. Therefore for probabilities in theory probability is close to 1 was situations big importance profession will reach.